Bile microbiota in gallbladder stones and its association with Helicobacter pylori: a systematic review and meta-analysis - Li, Hao; Zhang, Huiyao; Wu, Wenyu; Zhou, Tingting; Chen, Xiaoxiao; Yang, Yang; Wei, Wei (Frontiers in Microbiology, 2026)
IntroductionGallbladder stones (GS) is a prevalent gallstone disease. Recent studies indicate that bile microbiota dysregulation may contribute to their pathogenesis. However, the specific microbial alterations and their differences from gut microbiota patterns remain unclear. This study aimed to systematically evaluate the association between bile microbiota composition and GS.MethodsEligible studies comparing bile microbiota profiles between patients with GS and non-GS controls were retrieved from eight databases. Data on α- and β-diversity and microbial composition at the phylum and genus levels were extracted and synthesized.ResultsFor α-diversity, the abundance-based coverage estimator (ACE) index was higher in patients with GS compared with controls (SMD = 0.55, 95% confidence interval [CI]; 0.23–0.87), whereas the Chao1 (SMD = 0.51, 95% CI; −0.03–1.05) and observed species (SMD = 0.58, 95% CI; −0.03–1.19) showed positive but non-significant differences. The Simpson index was significantly higher in patients with GS (SMD = 0.49, 95% CI; 0.02–0.96). The Shannon index showed no overall difference (SMD = 0.03, 95% CI; −0.51–0.56), but was significantly decreased in the “GS vs. healthy controls (HC)” subgroup (SMD = −0.48, 95% CI; −0.94–-0.02). Analysis of β-diversity revealed that the bile microbiota of patients with GS differed significantly from that of control groups, although a few studies reported no significant differences. At the phylum level, patients with GS consistently exhibited increased Firmicutes and decreased Proteobacteria. At the genus level, enrichment of pathogenic taxa, such as Escherichia–Shigella and Streptococcus, was observed, whereas Helicobacter was elevated in only one study, indicating that its association with GS may be context-dependent and warrants further investigation.ConclusionGS is associated with bile microbiota dysbiosis, characterized by increased richness and potential overrepresentation of dominant taxa. These alterations differ from gut microbiota patterns in GS, suggesting a unique role of bile microbiota in GS pathogenesis.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251028569.